A Systematic Literature Review of Product Innovation, Digital Marketing, and Business Networking in Enhanching MSME Competities Through Digital Customer Engagement - Eko Alamsyah; Sudarmiatin Sudarmiatin; Agus Hermawan (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the influence of product innovation, digital marketing, and business networking on the competitiveness of small and medium-sized enterprises (SMEs), with customer engagement positioned as a mediating variable. Employing a Systematic Literature Review (SLR) approach, thirty Scopus-indexed articles published between 2020 and 2025 were analysed to synthesise theoretical and empirical insights related to SME competitiveness in contemporary digital and urban business environments. The findings indicate that product innovation, digital marketing, and business networking each play a significant role in strengthening SME competitiveness, particularly within markets characterised by rapid technological change. Customer engagement emerges as a critical mediating mechanism that connects these strategic variables to sustainable competitive advantage. It enhances the impact of innovative and digital strategies by fostering stronger emotional, behavioural, and participative interactions between SMEs and their customers. The review also highlights that SMEs adopting integrated digital management practices, such as the utilisation of human-resource information systems (HRIS) and data-driven decision-making tend to demonstrate greater adaptability, market responsiveness, and long-term performance. The study contributes theoretically by integrating resource-based and dynamic capability perspectives, offering a holistic understanding of how digital and relational capabilities interact to elevate competitiveness. Practically, the findings provide strategic guidance for policymakers, SME managers, and practitioners in designing innovation-oriented and digitally enabled initiatives that support sustainable SME growth in the digital era.